SISTEM INFORMASI SUMBANGAN PEMBINAAN PENDIDIKAN BERBASIS WEB PADA PONDOK PESANTREN TAHFIZHUL QURAN AL-IMAM ASHIM MAKASSAR - Djuanda Azis; Abdullah Tajuddin; Satriawaty Mallu (PROGRESS, 2022)
Payment of Sumbangan Pembinaan Pendidikan or abbreviated as SPP is a payment that is applied to every educational institution and has become the obligation of students to make SPP payments. One of them is at the Tahfizhul Quran Al-Imam Ashim Islamic Boarding School in Makassar. The system that is still used at the Tahfizhul Quran Al-Imam Ashim Islamic Boarding School Makassar still uses a manual system using a ledger in the data input process which is less effective so the process is required for inputting can be quite long. Manual systems can also have a bad impact on the input process, one of which is in the calculation section, in this case, not a few financial managers experienced this incident, this incident can cause problems in managing school management. Therefore, before this happens, the research team hopes to provide a solution to this problem, by suggesting using this web-based Payment Donation Information System to overcome this problem. The method used in this case is the waterfall developer method, Simple Additive Weighting, and Black Box Testing Method. Data collection techniques use qualitative techniques such as interviews, observations, and literature reviews. This information system has been designed according to the data we collect so that it can be used effectively and efficiently.